Implementation of Critical Thinking Values in Grade IV Indonesian Language Textbooks of The Merdeka Curriculum : A Content Analysis in The Application of The Pancasila Student Profile - Sadiah, Enok; Yanti, Prima Gusti; Tarmini, Wini (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to elaborate on the implementation of critical thinking values in several textbooks used in Indonesia as an essential aspect of the Pancasila Student Profile. The research approach utilized a qualitative content analysis method to examine elements of critical thinking in four Grade IV Indonesian Language textbooks within the Merdeka Curriculum, published by Erlangga, Yudistira, Bumi Aksara, and Kemendikbudristek. The findings showed that Grade IV Indonesian Language textbooks from these four publishers clearly implemented critical thinking characteristics, each with different emphases. Erlangga focuses on "Obtaining and Processing Information and Ideas," Yudistira emphasizes "Reflecting on Thought and Thought Processes," while Bumi Aksara highlights "Considering and Solving Problems." Lastly, the textbook from Kemendikbudristek also placed more focus on the "Considering and Solving Problems" element. Nevertheless, each textbook adopts a unique approach in fostering students' critical thinking and character development. Conceptually, the implementation of this study’s findings underscores the importance of varied approaches in teaching critical values, while practically encouraging educators and the curriculum to formulate balanced strategies for developing students’ skills in line with the Pancasila Student Profile.